Method for preparing ferrialite cement based on red mud and ferrialite cement
Patent Information
- Application Number
- CN202410769306.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-06-14
AI Technical Summary
[0003]现阶段使用赤泥制备铁铝酸盐水泥要解决的最关键问题是配料比例、烧结制度以及赤泥掺量问题;由于赤泥制备铁铝酸盐水泥需要进行烧结工艺以促使赤泥成型,而一般的烧结工艺需要温度在1250℃左右,但是在该烧结温度条件下过多的赤泥会造成铁铝酸盐水泥材料的板结,这导致了在制备铁铝酸盐水泥过程中赤泥的掺杂量普遍不高,使得最终制备得到的铁铝酸盐水泥材料的性能不足
[0024]本申请实施例提供了一种基于赤泥制备铁铝酸盐水泥的方法,所述方法包括:对赤泥原料进行搅拌,后进行干燥,以得到具有预设含水率的烘干物料;对所述烘干物料进行研磨,后进行筛分,以得到具有预设粒径的混合物料;对所述混合物料进行预热处理,后进行冷却,以得到预处理混合物料;将助熔剂与所述预处理混合物料进行混合,后进行挤压成型,以得到煅烧原料;对所述煅烧原料进行煅烧,以得到铁铝酸盐水泥;其中,所述助熔剂与所述预处理混合料的质量比≥0.03。助熔剂与预处理混合料的质量比可以≥0.03,可以促使预处理混合料有足量的助熔剂,足量的助熔剂可以有效地改善预处理混合料的成分和结构,以改善预处理混合料的熔融性,而改善了热熔融性的预处理混合料可以降低煅烧阶段的热量需求,从而可以降低煅烧阶段的温度,以避免赤泥大量的加入而造成铁铝酸盐水泥的板结,进而可以提高赤泥原料的加入量,另外足量的助熔剂可以促进预处理混合料中赤泥与其他组分的熔融反应,以增加铁铝酸盐水泥中玻璃相的含量,而足量的玻璃相可以提高铁铝酸盐水泥的粘合性和流动性,以容纳更多的赤泥原料,从而可以提高制备出的铁铝酸盐水泥的性能。
Smart Images

Figure CN118745087B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of recycling technology for solid waste from the aluminum industry, and in particular to a method for preparing aluminoferrite cement based on red mud and the aluminoferrite cement itself. Background Technology
[0002] Red mud is an industrial solid waste generated during the alumina refining process. Currently, an average of 1.0 to 2.0 tons of red mud are produced for every ton of alumina produced. Furthermore, the current comprehensive utilization rate of red mud is only 7.5%, leading to large-scale stockpiling. This stockpiling not only occupies land storage space and wastes land resources, but also easily causes environmental pollution and poses ecological safety hazards. Since red mud contains abundant iron and aluminum, as well as silicon dioxide, aluminum oxide, and iron oxide, and since current aluminoferrite cement mainly consists of anhydrous calcium sulfoaluminate, iron phase, and dicalcium silicate, using red mud as the main raw material to replace some of the raw materials in the preparation of aluminoferrite cement could fully utilize the unique component advantages of red mud.
[0003] The most critical issues to be addressed in the current preparation of aluminoferrite cement using red mud are the proportion of raw materials, the sintering process, and the amount of red mud added. Since the preparation of aluminoferrite cement using red mud requires a sintering process to promote the formation of the red mud, and the general sintering process requires a temperature of around 1250℃, excessive red mud at this sintering temperature will cause the aluminoferrite cement material to clump together. This results in a generally low amount of red mud added during the preparation of aluminoferrite cement, leading to insufficient performance of the final aluminoferrite cement material.
[0004] The current technology for preparing aluminoferrite cement using red mud includes: (1) using high-alkali red mud as raw material, mixing various conventional raw materials to form a round cake, then calcining it at 1125℃~1275℃, and then air-cooling it to prepare cement clinker. These cement clinker include sulfoaluminate cement clinker, silicate cement clinker or aluminoferrite cement clinker. In addition, calcium sulfate can be added before calcination to adjust the acidity and alkalinity in order to solve the problem of excessive alkali content; (2) first, red mud, steel slag, slag, desulfurized gypsum, silica fume, aluminum ash and other raw materials are successively processed through raw material grinding, homogenization, calcination at 1250℃~1300℃, clinker, grinding and other preparation stages to finally obtain aluminoferrite cement based on industrial solid waste. Then, the aluminoferrite cement based on industrial solid waste is mixed and stirred with recycled materials, water, foaming agent, aggregate, air-entraining agent and reinforcing materials to form a lightweight thermal insulation wall material. Summary of the Invention
[0005] This application provides a method for preparing aluminoferrite cement based on red mud and the aluminoferrite cement itself, in order to solve the following technical problem: how to improve the performance of aluminoferrite cement prepared based on red mud.
[0006] In a first aspect, this application provides a method for preparing ferroaluminate cement based on red mud, the method comprising:
[0007] The red mud raw material is stirred and then dried to obtain dried material with a preset moisture content;
[0008] The dried material is ground and then sieved to obtain a mixture with a preset particle size.
[0009] The mixture is preheated and then cooled to obtain a pretreated mixture.
[0010] The flux is mixed with the pretreated mixture and then extruded to obtain the calcined raw material.
[0011] The calcined raw materials are calcined to obtain aluminoferrite cement;
[0012] Wherein, the mass ratio of the flux to the pretreated mixture is ≥0.03.
[0013] Optionally, the mass ratio of the flux to the pretreated mixture is 0.1 to 0.03:1.
[0014] Optionally, the flux includes at least one of the following:
[0015] Calcium phosphate, calcium aluminum phosphate, borax, sodium borate, lithium salts, and lithium silicates.
[0016] Optionally, the preset moisture content is ≤0.5%.
[0017] Optionally, the preset particle size is ≤48μm.
[0018] Optionally, the preheating temperature is 140℃~200℃, and the preheating time is ≥3h.
[0019] Optionally, the calcination includes a heating section, the final temperature of which is 1070℃~1240℃.
[0020] Optionally, the calcination further includes a heat preservation section, the temperature of which is the final temperature of the heating section, and the heat preservation time is 30 min to 60 min.
[0021] Optionally, the mass ratio of red mud to the red mud raw material is 0.5 to 0.7.
[0022] Secondly, this application provides a ferroaluminate cement, which is prepared by the method described in the first aspect. By weight, the raw materials of the ferroaluminate cement include: red mud: 39 to 73 parts, desulfurized gypsum: 3 to 17 parts, high-alumina material: 2 to 8 parts, quicklime: 10 to 20 parts, fly ash: 5 to 10 parts, flux: 3 to 8 parts, carbon slag: 2 to 6 parts, and overhaul slag: 1 to 3 parts.
[0023] The technical solutions provided in this application have the following advantages compared with the prior art:
[0024] This application provides a method for preparing aluminoferrite cement based on red mud. The method includes: stirring red mud raw material and then drying it to obtain dried material with a preset moisture content; grinding the dried material and then sieving it to obtain a mixture with a preset particle size; preheating the mixture and then cooling it to obtain a pretreated mixture; mixing a flux with the pretreated mixture and then extruding it to obtain a calcined raw material; calcining the calcined raw material to obtain aluminoferrite cement; wherein the mass ratio of the flux to the pretreated mixture is ≥0.03. The mass ratio of flux to pretreated mixture can be ≥0.03, ensuring sufficient flux in the pretreated mixture. Sufficient flux can effectively improve the composition and structure of the pretreated mixture, thereby improving its meltability. Improved meltability reduces the heat requirement during calcination, thus lowering the calcination temperature and preventing the addition of large amounts of red mud that could cause caking of the aluminoferrite cement. This allows for an increase in the amount of red mud added. Furthermore, sufficient flux promotes the melting reaction between red mud and other components in the pretreated mixture, increasing the glass phase content in the aluminoferrite cement. Sufficient glass phase improves the adhesion and fluidity of the aluminoferrite cement, allowing it to accommodate more red mud, thereby enhancing the performance of the prepared aluminoferrite cement. Attached Figure Description
[0025] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0026] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1A schematic diagram of a method for preparing aluminoferrite cement based on red mud is provided in this application embodiment;
[0028] Figure 2 This is a schematic diagram of an aluminoferrite cement product provided in an embodiment of this application. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0030] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range such as 1, 2, 3, 4, 5, and 6, regardless of the range; in addition, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0031] In this document, terms including "comprising" and the like mean "including but not limited to". "At least one" means one or more, and "more than one" means two or more; "at least one", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items; for example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this application are commercially available or can be prepared by existing methods.
[0032] It should be noted that aluminoferrite cement possesses excellent impermeability. When the calcium sulfoaluminate hydration products of aluminoferrite cement are constrained by hydration space and other territorial limitations, the internal structure of the aluminoferrite cement extends into the voids, thus disrupting its structural channels. Furthermore, the hydration products of iron and aluminum colloids within the aluminoferrite cement continuously fill these voids. This combined effect minimizes the porosity of the concrete. Therefore, the internal mechanism of aluminoferrite cement's impermeability during its expansion differs from that of silicate cement. Moreover, the mutual compression between the hydrates within aluminoferrite cement creates an interconnected and interlocking structure, resulting in high crack resistance and impermeability.
[0033] Therefore, increasing the amount of red mud raw material can further improve the performance of aluminoferrite cement.
[0034] Figure 1 An exemplary schematic diagram of a method for preparing ferroaluminate cement based on red mud provided in an embodiment of this application is shown.
[0035] like Figure 1 As shown in the embodiments of this application, a method for preparing ferroaluminate cement based on red mud is provided, the method comprising:
[0036] S1. Stir the red mud raw material and then dry it to obtain dried material with a preset moisture content;
[0037] S2. Grind the dried material and then sieve it to obtain a mixture with a preset particle size;
[0038] S3. The mixture is preheated and then cooled to obtain a pretreated mixture;
[0039] S4. The flux is mixed with the pretreated mixture and then extruded to obtain the calcined raw material;
[0040] S5. The calcined raw material is calcined to obtain aluminoferrite cement;
[0041] Wherein, the mass ratio of the flux to the pretreated mixture is ≥0.03.
[0042] It should be noted that the raw material for red mud can be bulk solid waste related to the aluminum industry. These bulk solid wastes can be sintering red mud, desulfurized gypsum, high-alumina material (aluminum correcting material), quicklime, fly ash, carbon slag, or overhaul slag.
[0043] It should be noted that this extrusion molding can be used to form a cylindrical shape.
[0044] In some optional embodiments, the mass ratio of the flux to the pretreated mixture is 0.1 to 0.03:1;
[0045] In these embodiments, the mass ratio of flux to pretreated mixture can be 0.1 to 0.03:1, which can ensure that the pretreated mixture has a sufficient amount of flux. Sufficient flux can effectively improve the meltability of the pretreated mixture, thereby reducing the temperature during the calcination stage and avoiding the caking of aluminoferrite cement caused by the addition of a large amount of red mud. This can increase the amount of red mud raw material added. In addition, sufficient flux can increase the glass phase content in aluminoferrite cement. Sufficient glass phase can improve the adhesion and fluidity of aluminoferrite cement to accommodate more red mud raw material, thereby improving the performance of the prepared aluminoferrite cement.
[0046] The mass ratio of the flux to the pretreated mixture can be 0.1:1, 0.09:1, 0.08:1, 0.07:1, 0.06:1, 0.05:1, 0.04:1, or 0.03:1.
[0047] In some alternative embodiments, the flux includes at least one of the following:
[0048] Calcium phosphate, calcium aluminum phosphate, borax, sodium borate, lithium salts, and lithium silicates;
[0049] In these embodiments, the flux may include at least one of calcium phosphate, calcium aluminum phosphate, borax, sodium borate, lithium salt, and lithium silicate, which can help the flux effectively reduce the temperature during the calcination stage, thereby avoiding the caking of the aluminoferrite cement caused by the addition of a large amount of red mud, and thus increasing the amount of red mud raw material added to improve the performance of the prepared aluminoferrite cement.
[0050] It should be noted that this flux changes the compositional distribution of silicates, aluminates, ferrates, and calcium phosphates in aluminoferrite cement and promotes the melting reaction of these aluminoferrite cement components, thereby improving the sintering performance of aluminoferrite cement. In addition, this flux can improve the structural distribution of aluminoferrite cement, thereby further improving the melting performance of aluminoferrite cement.
[0051] It should be noted that this flux can promote the melting reaction of silicates and aluminates, thereby affecting the formation and changes of mineral phases in aluminoferrite cement. It can increase the amount of glass phase generated in aluminoferrite cement, and sufficient glass phase can increase the adhesion and fluidity of aluminoferrite cement, thereby improving the performance of the prepared aluminoferrite cement.
[0052] In some optional embodiments, the preset moisture content is ≤0.5%;
[0053] In these embodiments, the preset moisture content can be ≤0.5%, which facilitates subsequent grinding and sieving to obtain a mixture with a preset particle size. In addition, a preset moisture content of less than 0.5% can avoid the need for additional heat to evaporate moisture during the calcination stage, thereby effectively reducing the temperature during the calcination stage. This avoids the addition of a large amount of red mud, which could cause the aluminoferrite cement to caking. Consequently, the amount of red mud added can be increased to improve the performance of the prepared aluminoferrite cement.
[0054] In some alternative implementations, the preset particle size is ≤48μm.
[0055] In these embodiments, the preset particle size can be ≤48μm, which can make the mixture sufficiently fine. Sufficiently fine mixtures can be fully and uniformly mixed to promote sufficient calcination, thereby promoting the full formation of each phase in the aluminoferrite cement and avoiding excessive differences in the composition of the final aluminoferrite cement.
[0056] In some optional embodiments, the preheating temperature is 140℃~200℃, and the preheating time is ≥3h.
[0057] In these embodiments, the preheating temperature can be 140℃~200℃, and the preheating time can be ≥3h. This can promote the initial reaction of the high-alumina material in the red mud raw material, so as to convert the aluminum hydroxide component in the red mud raw material into aluminum oxide. This can complete the supplementation of aluminum corrector for the aluminoferrite cement, so as to promote the full formation of each phase component of the aluminoferrite cement. In addition, this preheating treatment can increase the heat of carbon-containing substances in the red mud raw material, so as to effectively reduce the calcination temperature in the subsequent calcination stage, so as to avoid the aluminoferrite cement from caking due to the large addition of red mud. This can increase the amount of red mud raw material added, thereby improving the performance of the prepared aluminoferrite cement.
[0058] The preheating temperature can be 140℃, 150℃, 160℃, 170℃, 180℃, 190℃ or 200℃.
[0059] In some alternative embodiments, the calcination includes a heating section, the endpoint temperature of which is 1070°C to 1240°C.
[0060] In these embodiments, calcination may include a heating section, and the end temperature of the heating section may be 1070°C to 1240°C. Heating can be used to meet the heat requirements of calcination, so as to cause the pretreated mixture to reach the phase change temperature quickly, thereby causing the calcined raw materials to be transformed into aluminoferrite cement products.
[0061] The final temperature of this heating section can be 1070℃, 1080℃, 1090℃, 1100℃, 1110℃, 1120℃, 1130℃, 1140℃, 1150℃, 1160℃, 1170℃, 1180℃, 1190℃, 1200℃, 1210℃, 1220℃, 1230℃, or 1240℃.
[0062] In some optional embodiments, the calcination further includes a heat preservation section, the temperature of which is the end temperature of the heating section, and the heat preservation section lasts for 30 to 60 minutes.
[0063] In these embodiments, calcination may also include a heat preservation section, the temperature of which is the end temperature of the heating section, and the heat preservation time may be 30 min to 60 min, which can promote complete phase transformation within the aluminoferrite cement to obtain aluminoferrite cement product with uniform composition distribution and stable structure; in addition, the energy consumption of calcination can be reduced while aluminoferrite cement is being generated, so as to save the energy cost of calcination.
[0064] The insulation time can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, or 60 min.
[0065] In some optional embodiments, the mass ratio of red mud to the red mud raw material is 0.5 to 0.7.
[0066] In these embodiments, the mass ratio of red mud to red mud raw material in the red mud raw material can be 0.5 to 0.7, which can promote the red mud raw material to have sufficient red mud. Sufficient red mud has sufficient aluminum phase and iron phase. After calcination, it can form a ferroaluminate cement product with uniform composition and stable structure. This indicates that the red mud doping amount in the ferroaluminate cement can account for more than half of the red mud raw material.
[0067] The mass ratio of red mud to red mud raw material in this red mud raw material can be 0.5, 0.6 or 0.7.
[0068] Figure 2 An exemplary schematic diagram of a ferroaluminate cement provided in an embodiment of this application is shown.
[0069] Based on a general inventive concept, such as Figure 2 As shown in the embodiment of this application, a ferroaluminate cement is provided. The ferroaluminate cement is prepared by the method described above. By weight, the raw materials of the ferroaluminate cement include: red mud: 39 to 73 parts, desulfurized gypsum: 3 to 17 parts, high-alumina material: 2 to 8 parts, quicklime: 10 to 20 parts, fly ash: 5 to 10 parts, flux: 3 to 8 parts, carbon slag: 2 to 6 parts, and overhaul slag: 1 to 3 parts.
[0070] The aluminoferrite cement is achieved based on the above method. The specific steps of the method can be referred to the above embodiments. Since the aluminoferrite cement adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.
[0071] It should be noted that in the composition of this aluminoferrite cement, the weight percentage of red mud can be 39 to 73 parts, and sufficient red mud can provide the aluminoferrite cement with sufficient aluminum and iron elements; the weight percentage of desulfurized gypsum can be 3 to 17 parts, and sufficient desulfurized gypsum can adjust the pH of the aluminoferrite cement; the weight percentage of high-alumina material can be 2 to 8 parts, and sufficient high-alumina material can be used as an aluminum corrector in the aluminoferrite cement; the weight percentage of quicklime can be 10 to 20 parts, and sufficient quicklime can absorb the carbon dioxide generated during calcination, thus avoiding the generation of large amounts of carbon dioxide during calcination that would affect the product quality of the aluminoferrite cement; and the weight percentage of fly ash can be 5 to 10 parts, and sufficient fly ash can supplement the aluminoferrite cement with silicon elements. The raw materials are: a calcium silicate phase to be generated during calcination; a flux of 3 to 8 parts by weight to provide sufficient flux for aluminoferrite cement to adequately reduce the calcination temperature, thereby increasing the amount of red mud raw material added; 2 to 6 parts by weight of carbon slag, which can be used as a fuel supplement to compensate for heat loss during calcination; and 1 to 3 parts by weight of overhaul slag, which contains sufficient cryolite and calcium fluoride. Sufficient cryolite and calcium fluoride can lower the melting point of the calcined raw materials to reduce the calcination temperature requirement. In addition, the overhaul slag can be used as a foaming agent during calcination to generate nitrogen and a small amount of carbon dioxide, thereby avoiding the toxic effects of carbon dioxide on aluminoferrite cement.
[0072] The red mud can be in the following weight proportions: 39 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, or 73 parts.
[0073] The desulfurized gypsum can be in the following weight proportions: 3 parts, 5 parts, 10 parts, 15 parts, or 17 parts.
[0074] The high-alumina material can be in parts by weight of 2, 3, 4, 5, 6, 7, or 8.
[0075] The quicklime can be in parts by weight of 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.
[0076] The fly ash can be in parts by weight of 5, 6, 7, 8, 9, or 10.
[0077] The flux can be in parts by weight of 3, 4, 5, 6, 7 or 8.
[0078] The weight of the charcoal slag can be 2, 3, 4, 5 or 6 parts.
[0079] The weight percentage of the overhaul slag can be 1 part, 2 parts, or 3 parts.
[0080] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to industry standards; if no corresponding industry standard exists, they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.
[0081] Example 1
[0082] like Figure 1 As shown, a method for preparing aluminoferrite cement based on red mud includes:
[0083] S1. Stir the red mud raw material and then dry it to obtain dried material with a preset moisture content;
[0084] S2. Grind the dried material and then sieve it to obtain a mixture with a preset particle size;
[0085] S3. The mixture is preheated and then cooled to obtain a pretreated mixture;
[0086] S4. The flux is mixed with the pretreated mixture and then extruded to obtain the calcined raw material;
[0087] S5. Calcining the raw materials to obtain aluminoferrite cement.
[0088] The mass ratio of flux to pretreated mixture is 0.03:1.
[0089] The flux is lithium salt.
[0090] The preset moisture content is 0.41%.
[0091] Preset particle size ≤ 48μm.
[0092] The preheating temperature is 200℃ and the preheating time is 3 hours.
[0093] The calcination process includes a heating section, with an end temperature of 1070℃ and a heating rate of 5℃ / min.
[0094] The calcination process also includes a heat preservation section, where the temperature is the same as the final temperature of the heating section, and the heat preservation time is 60 minutes.
[0095] A type of aluminoferrite cement, which is prepared by a method, wherein the raw materials of the aluminoferrite cement include, by weight: red mud: 39 parts, desulfurized gypsum: 17 parts, high alumina material: 8 parts, quicklime: 19 parts, fly ash: 10 parts, flux: 3 parts, carbon slag: 4 parts and overhaul slag: 3 parts.
[0096] Example 2
[0097] Based on the content disclosed in Example 1, the following modifications are made:
[0098] The mass ratio of flux to pretreated mixture is 0.05:1.
[0099] The flux is calcium phosphate.
[0100] The preset moisture content is 0.43%.
[0101] The preheating temperature is 180℃ and the preheating time is 3 hours.
[0102] The final temperature of the heating section is 1130℃, and the heating rate is 5℃ / min.
[0103] The heat preservation period is 50 minutes.
[0104] By weight, the raw materials for aluminoferrite cement include: red mud: 51 parts, desulfurized gypsum: 13 parts, high-alumina material: 7 parts, quicklime: 15 parts, fly ash: 9 parts, flux: 5 parts, carbon slag: 3 parts, and overhaul slag: 2 parts.
[0105] Example 3
[0106] Based on the content disclosed in Example 1, the following modifications are made:
[0107] The mass ratio of flux to pretreated mixture is 0.08:1.
[0108] The flux is borax.
[0109] The preset moisture content is 0.46%.
[0110] The preheating temperature is 160℃ and the preheating time is 3 hours.
[0111] The final temperature of the heating section is 1190℃, and the heating rate is 5℃ / min.
[0112] The heat preservation period is 40 minutes.
[0113] By weight, the raw materials for aluminoferrite cement include: red mud: 62 parts, desulfurized gypsum: 10 parts, high-alumina material: 5 parts, quicklime: 13 parts, flux: 8 parts, fly ash: 7 parts, carbon slag: 2 parts, and overhaul slag: 1 part.
[0114] Example 4
[0115] Based on the content disclosed in Example 1, the following modifications are made:
[0116] The mass ratio of flux to pretreated mixture is 0.08:1.
[0117] The flux is lithium silicate.
[0118] The preset moisture content is 0.48%.
[0119] The preheating temperature is 140℃ and the preheating time is 3 hours.
[0120] The final temperature of the heating section is 1240℃, and the heating rate is 5℃ / min.
[0121] The temperature of the heat preservation section is the same as the final temperature of the heating section, and the heat preservation time is 30 minutes.
[0122] By weight, the raw materials for aluminoferrite cement include: red mud: 73 parts, desulfurized gypsum: 7 parts, high-alumina material: 32 parts, quicklime: 10 parts, fly ash: 5 parts, carbon slag: 2 parts, and overhaul slag: 1 part.
[0123] Comparative Example 1
[0124] Based on the content disclosed in Example 4, the following modifications are made:
[0125] The red mud is 80 parts by weight.
[0126] Comparative Example 2
[0127] Based on the content disclosed in Example 4, the following modifications are made:
[0128] The red mud is 30 parts by weight.
[0129] Comparative Example 3
[0130] Based on the content disclosed in Example 4, the following modifications are made:
[0131] The cosolvent is 1 part by weight.
[0132] Comparative Example 4
[0133] Based on the content disclosed in Example 4, the following modifications are made:
[0134] The cosolvent is 10 parts by weight.
[0135] Comparative Example 5
[0136] Based on the content disclosed in Example 4, the following modifications are made:
[0137] The preheating temperature is 100℃.
[0138] Comparative Example 6
[0139] Based on the content disclosed in Example 4, the following modifications are made:
[0140] The preheating temperature is 300℃.
[0141] Comparative Example 7
[0142] Based on the content disclosed in Example 4, the following modifications are made:
[0143] The final temperature of the heating section is 1000℃.
[0144] The heat preservation period is 80 minutes.
[0145] Comparative Example 8
[0146] Based on the content disclosed in Example 4, the following modifications are made:
[0147] The final temperature of the heating section is 1300℃.
[0148] The heat preservation period is 20 minutes.
[0149] Relevant experimental and effect data:
[0150] The cement products obtained in each embodiment and comparative example were tested according to the "Standard Cement Mortar Strength Test".
[0151] The test was conducted according to the standard GB / T17671-1999, and the compressive strength of each cement product was counted on the third, seventh and twenty-eighth days of the test. The results are shown in Table 1.
[0152] Table 1. Compressive strength data of cement products from various embodiments and comparative examples.
[0153]
[0154]
[0155] As shown in Table 1, based on the data from Comparative Examples 1, 2 and 4, adding too much or too little red mud will result in insufficient strength of the final aluminoferrite cement product, or even prevent it from being further improved.
[0156] Furthermore, data from Comparative Examples 3, 4, and 4 show that if the amount of flux added is insufficient, a small amount of flux will lead to insufficient calcination, inadequate reaction between calcined raw materials, and ultimately insufficient content of effective phases in the aluminoferrite cement, affecting the performance of the aluminoferrite cement. In addition, if the amount of flux added is excessive, too much flux will remain in the final aluminoferrite cement, which will also lead to insufficient content of effective phases in the aluminoferrite cement, affecting the performance of the aluminoferrite cement.
[0157] Furthermore, data from Comparative Examples 5, 6, and 4 show that if the preheating temperature is too low or too high, it will lead to insufficient preheating or overheating, which will ultimately affect the heat replenishment during the calcination stage, preventing the calcination from proceeding fully. This will reduce the content of effective phases in the final aluminoferrite cement and affect the performance of the aluminoferrite cement.
[0158] Furthermore, data from Comparative Examples 7, 8, and 4 show that excessively high or low calcination temperatures, as well as excessively long or short holding times, will affect the heat generated during the calcination stage, preventing the calcination from proceeding sufficiently. This will reduce the content of effective phases in the final aluminoferrite cement and affect its performance.
[0159] In summary, the method for preparing aluminoferrite cement based on red mud provided in this application can effectively improve the composition and structure of the pretreated mixture by adding flux before calcining the red mud raw material, thereby improving the meltability of the pretreated mixture and increasing the amount of red mud raw material added. In addition, sufficient flux can increase the glass phase content in the aluminoferrite cement to accommodate more red mud raw material, thereby improving the compressive strength of the prepared aluminoferrite cement.
[0160] In addition, the present application provides a method for preparing aluminoferrate cement based on red mud, which uses a flux to lower the calcination temperature, effectively reducing the energy consumption of the entire preparation method and saving energy in the preparation stage, so as to realize the large-scale application of red mud.
[0161] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A method for preparing aluminoferrite cement based on red mud, characterized in that, The method includes: The red mud raw material is stirred and then dried to obtain dried material with a preset moisture content; The dried material is ground and then sieved to obtain a mixture with a preset particle size. The mixture is preheated and then cooled to obtain a pretreated mixture. The flux is mixed with the pretreated mixture and then extruded to obtain the calcined raw material. The calcined raw materials are calcined to obtain aluminoferrite cement; Wherein, the mass ratio of the flux to the pretreated mixture is ≥0.03; The mass ratio of red mud to the red mud raw material is 0.5 to 0.
7. The raw materials of the aluminoferrite cement include: red mud: 39 to 73 parts, desulfurized gypsum: 3 to 17 parts, high alumina material: 2 to 8 parts, quicklime: 10 to 20 parts, fly ash: 5 to 10 parts, flux: 3 to 8 parts, carbon slag: 2 to 6 parts, and overhaul slag: 1 to 3 parts.
2. The method according to claim 1, characterized in that, The mass ratio of the flux to the pretreated mixture is 0.1 to 0.03:
1.
3. The method according to claim 1 or 2, characterized in that, The flux includes at least one of the following: Calcium phosphate, calcium aluminum phosphate, borax, sodium borate, lithium salts, and lithium silicates.
4. The method according to claim 1, characterized in that, The preset moisture content is ≤0.5%.
5. The method according to claim 1, characterized in that, The preset particle size is ≤48μm.
6. The method according to claim 1, characterized in that, The preheating temperature is 140℃~200℃, and the preheating time is ≥3h.
7. The method according to claim 1, characterized in that, The calcination includes a heating section, the final temperature of which is 1070℃~1240℃.
8. The method according to claim 7, characterized in that, The calcination process also includes a heat preservation section, the temperature of which is the final temperature of the heating section, and the heat preservation time is 30 min to 60 min.
9. A type of aluminoferrite cement, characterized in that, The aluminoferrite cement is prepared by the method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing high-iron cement by utilizing red mud
CN103833245A